The dialogic nature of the wagon and its communicative intentions (on the material of the universal I UCR) - Гуменяк, Віра Олександрівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”)
The article is devoted to the study of the dialogical nature of the First Wagon UCR and characteristics of communicative intentions, defining and organizing the content of the text. Analyzed the notion of dialogicality as important signs of the text, we considered a model of interaction between the sender and the addressee and means of their expression in the text of the Universal, described the forms of expression of dialogicality identified and characterized intertextual communication station Wagon.